SAT0464 The ideal target for psoriatic arthritis? comparison of remission and inactive disease states in a real life cohort. (15th June 2017) - Mens, LJJ Van; Kuijk, AWR van; Baeten, DL; Coates, LC
Abstract : Background: Recommendations on psoriatic arthritis (PsA) state that the target of treatment should be remission or inactive disease. Multiple potential targets have been developed and proposed, each with a different composition of clinical measurements. Objectives: Our aim is to use an existing real life dataset of a large group of patients in a low disease activity state, to compare different targets and provide further evidence to choose a target. Methods: This analysis uses data from a cross-sectional real life cohort of 250 PsA patients (EULAR16–2124). All patients were considered in an acceptable disease state according to the treating rheumatologist, defined by the fact that the rheumatologist did not consider to modify the current treatment. Remission/inactive disease targets were the DAPSA [TJC; SJC; patient global visual analogue scale (Pt VAS); pain VAS; CRP] and clinical (c)DAPSA [DAPSA minus CRP] remission (≤4), very low disease activity (VLDA) [7/7 of TJC ≤1; SJC ≤1; PASI ≤1; Pt pain ≤15mm; Pt VAS ≤20mm; HAQ ≤0.5; tender entheseal points ≤1], and PASDAS ≤1.9 or near remission (NR). Results: 113 pts were in cDAPSA remission, 107 in DAPSA remission, 56 met VLDA and 37 in PASDAS NR. There was a very high percentage exact agreement between DAPSA and cDAPSA (96%) reflecting the similarity of the two definitions. DAPSA/cDAPSA and VLDA show a high correlation (pearson of 0, 611 and 0, 590 resp) but VLDA is more stringent in comparison with both DAPSA scores. The correlation between NR and DAPSA/cDAPSA/VLDA was lower, (pearson 0, 400, 0, 403 and 0, 412 resp). Again PASDAS NR was generally more stringent than DAPSA/cDAPSA remission but greater dissimilarities are seen between PASDAS NR and VLDA where 14 patients are in VLDA but not PASDAS NR and 29 are in PASDAS NR but not VLDA. Although presence of active joint disease was similar across the different measures, VLDA presents as a more stringent cutoff with less residual disease in PASI, TJC and less impact on DLQI and HAQ. All targets had similar % of patients with a raised CRP. The DAPSA measures which do not include an enthesitis measure show more patients with an active enthesitis. There was a limited consequence on QoL measures when residual disease activity was allowed in certain domains in these remission states. In those patients with active enthesitis or skin disease, no differences were found on PROs on quality of life and functionality. The presence of active skin disease with a PASI>2 (present in 20/110 pts achieving DAPSA) was reflected by an impact on DLQI (2, 85 (SD2, 9)v.s. 1 (2, 3)p=0.003). This effect was not seen when the cutoff of for PASI>1 was used. Conclusions: This comparison of the different remission targets shows that VLDA presented as the most stringent target. Inclusion of laboratory markers seems not to be a necessity although the exclusion of a skin domain might result in a negligence of skin disease in some patients despite an impact on their QoL. Disclosure of Interest: L. Van Mens: None declared, A. van Kuijk Grant/research support from: UCB, Pfizer, MSD, Janssen, Consultant for: Novartis, Celgene, D. Baeten Grant/research support from: Pfizer, MSD, AbbVie, UCB, Novartis, Janssen, Boehringer Ingelheim. This cohort was funded by an unrestricted grant from Pfizer to DB, Consultant for: Pfizer, MSD, AbbVie, UCB, Novartis, Janssen, Boehringer Ingelheim, Eli Lilly, Roche, BMS, Glenmark, Employee of: UCB, L. Coates: None declared